Radiological External Picture of Proximal Humerus Fracture After Surgery at Haji Adam Malik Hospital - Teuku Reza Syahputera Sofyan; Nino Nasution; Pranajaya Dharma Kadar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Proximal humerus fractures are among the most common musculoskeletal injuries, particularly in elderly patients with decreased bone density. Open Reduction and Internal Fixation (ORIF) is a widely used surgical technique aimed at restoring anatomical alignment and achieving stable fixation. This study aimed to evaluate postoperative radiological outcomes of proximal humerus fractures treated with ORIF at H. Adam Malik Hospital, Medan. This research employed a descriptive observational design with a cross-sectional approach using retrospective data from medical records of patients treated between January 2021 and December 2024. A total of 25 patients who met the inclusion criteria were analyzed. Radiological parameters assessed included neck-shaft angle (NSA), humeral head height (HHH), medial offset (MO), medial hinge gap (MHG), and acromiohumeral interval (AHI). Measurements were conducted by two independent observers, and inter-observer reliability was evaluated using the Intraclass Correlation Coefficient (ICC). The results showed that the majority of patients were female (68%), with the largest age group being 18–49 years (44%). The inter-observer reliability demonstrated excellent agreement (ICC = 0.947). The mean values of radiological parameters were: NSA 127.83° ± 7.28°, HHH 8.87 ± 1.72 mm, MO 8.74 ± 2.97 mm, MHG 2.28 ± 0.73 mm, and AHI 7.60 ± 1.37 mm. These findings indicate that most parameters were within normal limits, although NSA tended toward mild varus alignment and MHG exceeded the ideal anatomical threshold. In conclusion, postoperative radiological outcomes of proximal humerus fractures treated with ORIF generally showed acceptable alignment and fixation stability. However, attention to medial support restoration is necessary to prevent complications such as varus collapse. Radiological evaluation remains essential for assessing surgical success and predicting functional outcomes.